Introduction. Sayad and Migrants’ Descendants: A Renewed Gaze - Calabretta, Andrea; Ragone, Marianna; Avallone, Gennaro (Italian Sociological Review, 2025)
Despite being widely known and cited, Abdelmalek Sayad remains an author subject to divergent representations and interpretations and frequently reduced to a superficial use of some of his most famous concepts. Contrary to this simplifying reading, Sayad’s work crosses different fields of study and is characterised by a particular reflexive depth. Through migration, the author is able to analyse the dynamics of social and symbolic inclusion and exclusion, the construction and modification of social hierarchies at both local and international levels, and social change and conflict at large. In this sense, Sayad also offers important and little explored keys to understanding the experiences and trajectories of the children of migration. This introductory contribution aims to draw attention to the way Sayad has studied migrants’ descendants, highlighting how his approach is helpful for the renewal of this field of study. The contribution concludes with a presentation of the papers that are part of this Special Issue.